Detection of Microplastics in the Digestive Tract of Commercial Fishes from Swalayan X Yogyakarta City - Suwartiningsih, Nurul; Aprilda, Clariza Ninda; Putra, Ichsan Luqmana Indra; Putra, Sigit Surya (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Plastic waste in waters can be degraded into microplastics with a size <5 mm. Microplastics in waters can enter the bodies of organisms, including commercial fishes. This study aims to analyze the abundance and characteristics of microplastics in the digestive tract of three species of commercial fishes from Supermarket X, Yogyakarta City, DIY Province. This study is an exploratory research that used three species of fishes, milkfish (Chanos chanos), mackerel (Rastrelliger sp.), and tuna (Euthynnus affinis). Fish samples were purchased from Supermarket X, Yogyakarta City, DIY Province, taken using quota sampling technique. The fish digestive tract was taken, soaked in 10% KOH, heated in oven at 60° then filtered. The obtained microplastics were then observed under a light microscope. The Kruskal Wallis test was performed to differentiate the abundance and characteristics of microplastics among the three species of fishes. The results showed the abundance of microplastics in the digestive tract of mackerel 465.00 ± 222.69 microplastics/individual, milkfish 471.67 ± 58.53 microplastics/individual and tuna 554.00 ± 122.19 microplastics/individual, but not significantly different. The forms of microplastic found were fiber, fragments, films, and pellets but not significantly different. The color of the microplastics obtained were not significantly different between fish species. Microplastics are dominated by the size range of 101 – 200 µm. Based on the FT-IR results, the microplastics found were Polypropylene (PP). Microplastics detected in the digestive tract of three species of commercial fishes from Supermarket X, Yogyakarta City, DIY Province have abundance and characteristics that are not significantly different.